Learning Interest: An Experimental Study of the SAVI (Somatic, Auditory, Visual, Intellectual) Learning Model - Kharisma, Kharisma; Erlina, Erlina; Sunarto, Sunarto (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The most significant hurdle to Islamic religious education and character education learning at vocational school was pupils' low enthusiasm in learning, especially in participation and attentiveness. Traditional learning approaches might not suit all student styles. Thus, this study seeks to empirically evaluate the SAVI learning model (Somatic, Auditory, Visual, Intellectual) compared to standard learning approaches in enhancing student interest in learning. This quantitative study used a quasi-experimental posttest-only control group design. At Vocational School 1 Bandar Lampung, grade XI pupils were divided into two groups: the experimental class (provided the SAVI model therapy) and the control class (given the conventional method treatment). The instrument was a learning interest questionnaire. Analysis included precondition tests (normality and homogeneity) and t-tests. The study confirmed normality (Sig. > 0.200) and homogeneity (Sig. Levene's Test = 0.601). A 2-tailed hypothesis test significance value of 0.031 was obtained. The null hypothesis (H0) is rejected because this value is less than 0.05, showing a significant learning interest difference. The mean difference value of 3.4667 shows that SAVI-taught students had considerably higher learning interest than the control group. This interest boosts targeted deficits in pupils' desire to learn. This study suggests an innovative learning paradigm that boosts interest in Islamic religious education and character education. This study supports the holistic learning approach, which stresses combining physical, aural, visual, and intellectual aspects to engage students.